Factors influencing interdepartmental information sharing practice in electronic government agencies - Kamal, Mohd Razalan; Valbir Singh, Dalbir Singh; Ahmad, Kamsuriah (2012)
Electronic information sharing is a key to effective government.This study is conducted to investigate the factors influencing interdepartmental information sharing (IS) practice in electronic government (EG) agencies.Based on previous study and observation, the issues on electronic government and information sharing are highlighted and the influencing factors are identified. Three domains of factors that are considered in this study are individual, organizational and technological factors. This paper proposes the conceptual framework of interdepartmental information sharing for electronic government agencies in Malaysia.